2006
DOI: 10.1074/jbc.m601968200
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin Is Required for Deoxyribonucleotide Pool Maintenance during S Phase

Abstract: Thioredoxin was initially identified by its ability to serve as an electron donor for ribonucleotide reductase in vitro. Whether it serves a similar function in vivo is unclear. In Saccharomyces cerevisiae, it was previously shown that ⌬trx1 ⌬trx2 mutants lacking the two genes for cytosolic thioredoxin have a slower growth rate because of a longer S phase, but the basis for S phase elongation was not identified. The hypothesis that S phase protraction was due to inefficient dNTP synthesis was investigated by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 28 publications
2
56
0
2
Order By: Relevance
“…Although the DNA damage response and dNTP synthesis pathways of yeast and mammals have significant similarities, it is neither clear why mammalian cells do not show an increase in the sizes of their dNTP pools nor how they perform the repair process in the event of DNA damage. Our dNTP pool measurements in wild-type and rad53-11 mutant cells were consistent with previously published results [7,[13][14][15]. In one of our previous studies, similar dNTP levels were observed for asynchronous rad53-11 cells, and mutants did not show any cell-cycle perturbations when analysed by flow cytometry, which suggested that rad53-11 cells operate under a normal cell-cycle progression.…”
Section: Discussionsupporting
confidence: 92%
“…Although the DNA damage response and dNTP synthesis pathways of yeast and mammals have significant similarities, it is neither clear why mammalian cells do not show an increase in the sizes of their dNTP pools nor how they perform the repair process in the event of DNA damage. Our dNTP pool measurements in wild-type and rad53-11 mutant cells were consistent with previously published results [7,[13][14][15]. In one of our previous studies, similar dNTP levels were observed for asynchronous rad53-11 cells, and mutants did not show any cell-cycle perturbations when analysed by flow cytometry, which suggested that rad53-11 cells operate under a normal cell-cycle progression.…”
Section: Discussionsupporting
confidence: 92%
“…It has recently been reported that the physiological factor for ribonucleotide reduction is thioredoxin, which is required for the RR reaction in vitro (Koc et al, 2006). In yeast, mutants lacking thioredoxin had significantly lower dNTP levels, supporting the idea that thioredoxin functions as an RR reductant in vitro.…”
Section: Discussionmentioning
confidence: 90%
“…In all eukaryotic systems that were examined, with the exception of our studies, DTT is used as the reductant to allow RNR to catalyze multiple turnovers, rather than the endogenous reductant, thioredoxin and thioredoxin reductase (76). In our hands when α is assayed with excess ββ′, the activity is reduced several-fold with DTT in place of the protein reducing system (data not shown).…”
Section: Specific Activity Measurements Suggest That Rnr Need Not Be mentioning
confidence: 88%
“…From our data, and the range of specific activities for α n and ββ′, the number of dNTPs produced can be calculated to vary between 3.6 × 10 8 and 1.1 × 10 9 , a 10-100-fold excess over the requirements for genome replication. Recent dNTP pool measurements by Merrill and co-workers indicate that in asynchronous wt S. cerevisiae cells (W303) there are 1.8 × 10 6 dNTPs, only 10% of the pool size minimally required to replicate the whole genome (76). Thus, the low levels of dNTPs measured by Koc et al suggest that RNR activity is greatly reduced in vivo.…”
Section: Specific Activity Measurements Suggest That Rnr Need Not Be mentioning
confidence: 99%